Alcohol use, suicidality and virologic non-suppression among young adults with perinatally acquired HIV in Thailand: a cross-sectional study - Aurpibul L. (2023)
Introduction: Young adults with perinatally acquired HIV (YA-PHIV) are facing transitions to adult life. This study assessed health risk behaviours (including substance use), mental health, quality of life (QOL) and HIV treatment outcomes of Thai YA-PHIV. Methods: A cross-sectional study was conducted in Thai YA-PHIV aged 18–25 years who were enrolled in a prospective cohort study at five tertiary paediatric HIV care centres in Thailand. Study data were obtained through face-to-face interviews from November 2020 to July 2021. Assessments were performed for alcohol use (Alcohol Use Disorders Identification Test; AUDIT), smoking (Fagerstrom Test for Nicotine Dependence), drug/substance use (Drug Abuse Screening Test; DAST-10), depression (Patient Health Questionnaire for Adolescents; PHQ-A), anxiety (Generalized Anxiety Disorder; GAD-7) and QOL (World Health Organization QOL Brief-Thai). HIV treatment outcomes were extracted from the National AIDS Program database. Results: Of 355 YA-PHIV, 163 (46%) were males: their median age was 21.7 (interquartile range, IQR 20.2–23.5) years. There were 203 YA-PHIV (58%) who reported ever having sex; 141 (40%) were sexually active in the past 6 months, of whom 86 (61%) reported 100% condom use. Overall, 49 (14%) met the criteria for harmful alcohol use; 28 (7.9%) were alcohol dependent. Sixty (17%) were current smokers and 37 (11%) used drugs/substances. The frequency of moderate up to severe symptoms for depression was 18% and for anxiety was 9.7%. Their overall QOL was good in 180 (51%), moderate in 168 (47%) and poor in five (1.4%). There were 49 YA-PHIV (14%) with CD4 <200 cells/mm3 and 85 (24%) with virologic non-suppression (HIV-RNA >200 copies/ml). On multivariate analyses, the highest education at the primary to high school or vocational school levels (adjusted odds ratio [aOR] 2.02, 95% CI 1.40–3.95, p 0.04), harmful alcohol use (aOR 2.48, 95% CI 1.24–4.99, p 0.01), alcohol dependence (aOR 3.54, 95% CI 1.51–8.31, p <0.01) and lifetime suicidal attempt (aOR 2.66, 95% CI 1.11–6.35, p 0.03) were associated with non-suppression. Conclusions: Regular screening for alcohol use and mental health, including suicidality, would be useful to identify YA-PHIV who need more intensive psychosocial support or referral services to ensure they can achieve and maintain a high QOL into adult life.